2016
DOI: 10.1590/0074-02760160166
|View full text |Cite
|
Sign up to set email alerts
|

Candida duobushaemulonii: an emerging rare pathogenic yeast isolated from recurrent vulvovaginal candidiasis in Brazil

Abstract: The aim of this study was to identify Candida species isolated from women diagnosed with recurrent vulvovaginal candidiasis (RVVC) and their partners; and to evaluate the fluconazole (FLZ) susceptibility of the isolates. In a period of six years, among 172 patients diagnosed with vulvovaginal candidiasis, 13 women that presented RVVC and their partners were selected for this investigation. The isolates were obtained using Chromagar Candida medium, the species identification was performed by phenotypic and mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 22 publications
0
16
0
1
Order By: Relevance
“…amphotericin B [54]. Other Brazilian studies reported C. haemulonii complex isolates with low susceptibility to fluconazole or amphotericin B [58,59]. These data suggest that although these species are rare, they could be clinically relevant, and their correct identification is recommended.…”
Section: Discussionmentioning
confidence: 74%
“…amphotericin B [54]. Other Brazilian studies reported C. haemulonii complex isolates with low susceptibility to fluconazole or amphotericin B [58,59]. These data suggest that although these species are rare, they could be clinically relevant, and their correct identification is recommended.…”
Section: Discussionmentioning
confidence: 74%
“…vulnera form a fungal complex (named C. haemulonii complex) that is represented by emergent, opportunistic yeasts able to cause human infections with a wide range of clinical manifestations, varying from superficial to deep-seated infections, especially in individuals with immunocompromising health conditions [1]. In this sense, the main isolation sites of the C. haemulonii species complex described in the literature are blood, foot ulcers, nails, bones, skin wounds, and vagina; however, there are reports of isolates obtained from other body fluids such as cerebrospinal fluid, bronchoalveolar lavage, vaginal discharge, pleural effusion, peritoneal and ascitic fluids, bile, and urine [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Differential diagnosis of vulvovaginal candidiasis from bacterial vaginitis and trichomoniasis is difficult based on signs and symptoms and leads to suboptimal care (7). tion by non-albicans species, such as C. glabrata, has increased (5,8). In addition, the correct identification and differentiation of etiological agents is very important for early treatment and preventing of invasion (9).…”
Section: Introductionmentioning
confidence: 99%